The real-time Monitoring of TEG using the LabVIEW Technique for Green Energy Generation - Saleh , Umar Abubakakar; Jumaat, Siti Amely; Muhammad Akmal, Johar; Wan Jamuludin, Wan Akashah (Multidisciplinary Applied Research and Innovation, 2021)
The continuing rise in the cost of fossil fuels and their harmful effects on the environment have encouraged researchers to explore inward for an alternative source of energy. Through the Seebeck effect, thermoelectric generators (TEGs) have exhibited their ability to convert heat energy directly into electrical energy. Thermoelectric systems have emerged as a promising alternative to the existing technologies for green energy generation in the recent decade due to their unique characteristics. TEGs are also eco-sustainable, which operate quietly considering they lack mechanical systems or rotational parts. Therefore, they can be produced on a wide range of substrates, notably polymers, silicon, and ceramics. The real-time monitoring of the TEG devices is vital for determining the future utilisation of the technology and the green energy need. This project, therefore, presents the real-time monitoring of TEG using the LabVIEW Technique for green energy generation. The system monitor and records both electrical parameter and the temperature. The electrical data includes the TEG current, voltage and power, while the temperature data includes the shingle, TEG, and ambient temperature. The TEG was placed at the backside of the shingle under the photovoltaic panel of the test ring residential roof structure sloped at 30o. National Instruments (NI DAQ) unit was used as the data logger. The results indicate a 10.99 V and 0.099 A at a temperature difference of 3.56oC, showing efficiency in the power output of 4.5 %. A thermoelectric generator is a solid and reliable technology used in a wide range of applications such as green agriculture, aerospace, medical, residential and industrial sector for energy generation that is free from emissions for a sustainable and green environment.